2019
DOI: 10.1108/ijem-02-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Gender, school leadership and teachers’ motivations

Abstract: Purpose The research investigates perceptions of teachers in the Arab education system in Israel concerning the effect of their principal’s leadership and gender on their motivation. Relying on Hofstede’s cultural dimensions as an analytic tool to understand the Arab school, the purpose of this paper is to answer the following research questions: first, how do the teachers perceive the leadership style and gender of their principal and what influence do these perceptions have on their motivation? Second, what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
(63 reference statements)
1
13
1
Order By: Relevance
“…These results can be explained by several factors. First, the shift from peasantry to work in the general employment market has carried about a releasing of the ties of the extended Arab family in Israel (Massry-Herzallah & Arar, 2019). Second, increase in the percentage of Arab students studying in higher education institutions with new professional aspirations This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be explained by several factors. First, the shift from peasantry to work in the general employment market has carried about a releasing of the ties of the extended Arab family in Israel (Massry-Herzallah & Arar, 2019). Second, increase in the percentage of Arab students studying in higher education institutions with new professional aspirations This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dwairy and Van-Sickle (1996), since the beginning of childhood, traditional social norms of Arab society prepare the individual to choose conformity. For instance, teachers in Arab society perceive the job of the principal as essentially a man’s job with an autocratic and nonparticipative style of management and male domination (Massry-Herzallah & Arar, 2019). Nevertheless, in recent decades, a process of “Israelisation” has taken place through which the Arab minority or certain groups or individuals within this society experience modernization, marked by rising living and educational standards and a rise in the status of women (Nassir & Benoliel, 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Why did the moderating role of the TLS in the correlation between the frequency of OT and improvement of TPACK only appear among AT? A possible explanation may stem from the description of Arab school leadership style as an authoritarian style (Masry-Herzallah and Arar, 2019), in contrast to the TLS adopted in Jewish schools (Shapira-Lishchinsky and Litchka, 2018). Therefore, the correlation between frequency of OT and ATs` TPACK depended on the level of TLS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is relatively little empirical literature bearing on the changes experienced by Israeli students and teachers resulting from ethnic socialization. Furthermore, much of this empirical literature has focused on the relationship between socialization experiences and ethnic identity (Da'as, 2017;Da'as & Zibenberg, 2019;Hadad et al, 2020;Massry-Herzallah & Arar, 2019). Therefore, the present research relies on Hofstede's dimensional paradigm (Hofstede, 1980(Hofstede, , 2001, which contributes to a better understanding of the mechanisms and implications of the culture-related differences.…”
Section: Digital Forms Of Information and Communication Are Transformingmentioning
confidence: 99%
“…In order to learn in their own language and preserve their cultural identity students belonging to these ethnic groups mostly choose to attend Arabic‐speaking schools, which teach the same subject‐matter (e.g., math, English) required for all state‐funded schools (Blau, 2014; Maoz, 2005; Yashiv & Kasir, 2014). Nevertheless, studies have found that there are unique cultural differences between the Arabic‐speaking minority and the Hebrew‐speaking population in Israel, and these differences have implications on the education system in relation to the knowledge, skills, and trends observed in the education system (Abu Rahmoun et al, 2021; Da'as, 2017; Hadad et al, 2020; Massry‐Herzallah & Arar, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%